The Controversy of PBESI vs MPL Indonesia on Social Media: Crisis Communication Insights - Krisdian Majid Bella Vigata; Flavia Maharani Yunazar (Mahesa Research Center, 2023)
This article aims to investigate the emerging issues in the regulation of online gaming in Indonesia. Specifically, it focuses on the regulatory violation claim case that has been filed by MPL Indonesia against the regulations issued by PBESI, which governs the Implementation of Esports Activities in Indonesia based on PBESI Regulation No: 034/PB-ESI/B/VI/2021. To approach this issue, we adopt the theoretical framework of crisis communication. The data we use in this research is collected through qualitative analysis methods, specifically Qualitative Content Analysis (QCA). Our data sources come from various scientific references and related literature. The results of our analysis show that the regulatory violation claim filed by MPL Indonesia cannot be upheld based on existing empirical evidence. Therefore, we argue that it is necessary to review the claim and resolve it based on crisis communication principles that emphasize the importance of clear messaging, consistency, and transparency. Thus, it is hoped that it can avoid protracted polemics and harm the Mobile Legends Community: Bangbang Community and the esports industry as a whole.